The Influence of Work Discipline and Work Ethics on Employee Performance at the Cisaranten Bina Harapan Village Service - Nugraha, Andyka Fajar; Oktafien, Shinta (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
A government agency with the position of Civil Servants as elements of the State apparatus who serve as public servants must provide services fairly to the community based on loyalty and obedience to Pancasila and the 1945 Constitution. To carry out their duties properly, employee development is directed to improve the quality of human resources in order to have attitudes and behaviors that have the core of devotion, honesty, professionalism, responsibility, discipline, work ethic, organizational commitment and authority so that they can provide services in accordance with the demands of community development. Lately, in some government agencies there are weaknesses in providing services to the community which can be seen from the work discipline and work ethic of their employees. This study aims to determine the effect of work discipline and work ethic on employee performance at the Cisaranten Bina Harapan Village Office. The population used in this study were 36 respondents. The sampling technique used is saturated sampling by observing and distributing questionnaires to 36 respondents. The data analysis technique used classical assumption test which included: normality test, heteroscedasticity test, and multicollinearity test and multiple linear regression analysis. The results showed that work discipline partially had no effect on employee performance, work ethic partially affected employee performance. Meanwhile, based on the multiple linear regression equation, work discipline and work ethic simultaneously affect employee performance.